Conservation of cultural heritage in minority ethnic regions in northwestern china—an exploration at Kuqa, Xinjiang (Copernicus Publications, 2018)
Kuqa, Xinjiang, is located at northwestern inland china. Traditionally a bridge between eastern and western civilizations, Kuqa had a history of cultural fusion and was left with abundant cultural heritage. As population increase, economic growth and social changes occurred, spontaneous renovation of the old city was affected, in which street fabric and scenes underwent damages. The paper demonstrates attempts made in various projects to achieve conservation of cultural heritage in agreement with economic development and improvement of living condition. The lessons learnt in these projects will be of value to development of other historic cities, especially in minority ethnic regions in China.